Calculation Formulas in the Statement of Cash Flows Prepared According to the Polish Regulations – Proposals for Changes - Kawa, Barbara (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The paper questions the legitimacy of using certain signs (“+”, “–”) for the calculation formulas used to state cash flows laid down by Polish accounting law.Research Design & Methods: Deductive and inductive methods relating to the structure and content of the cash flow statement were used.Findings: The paper points out that, in the statement of cash flows where the cash flows of operating activities are presented indirectly, the position Net cash flows of operating activities should be determined by adding the following positions: Net profit (loss) and Adjustments total. The paper also indicates that in the statement of cash flows, regardless of how the cash flows from operating activities are presented, the position total Net cash flows is always equals to the sum of the following cash flows: operating, investing and financing. Likewise, the position Cash at the end of the period is always equal to the sum of the following: Cash at the beginning of the period and total Net cash flows. Finally, the paper presents an alternative way of grouping the adjustments used in the statement of cash flows, where the operating activities are presented indirectly.Implications / Recommendations: Some of the given calculation formulas included in Annex No 1 to the Polish Accounting Act need to be reconsidered and, probably, amended. The following changes are proposed:– in the statement of cash flows, where the cash flows of operating activities are presented indirectly: position A.III Net cash flows of operating activities: I + II (instead of I +/– II);– in the statement of cash flows, regardless of how cash flows from operating activities are presented: position D. Net cash flows total: A.III + B. III + C.III (instead of A.III +/– B.III +/– C.III); position G. Cash at the end of the period: F + D (instead of: F +/– D).Contribution: The paper elaborates the need to unambiguously use the “+” and “–“ signs in the statement of cash flows and consequently the need to change the calculation formulas included in the statement of cash flows defined by the Polish Accounting Act. The proposed changes, based on both theory and legal regulations, should improve the quality of financial statements.